The Role of Company Size in the Influence of Sustainability Practices on Financial Performance - Safitri, Linda Eka; Zahara, Inna (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Sustainability issues encourage manufacturing companies to focus not only on profitability but also on environmental responsibility. Green accounting practices, ISO 14001, and innovations in green technology are strategies for managing environmental impacts. Using regression analysis, this study analyzed secondary data from 55 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period from 2019 to 2023. The quantitative data that has been collected is processed and analyzed using the Statistical Package for the Social Sciences (SPSS) software. Multiple linear regression analysis models and Moderated Regression Analysis (MRA) are used to examine the relationship between independent variables (green accounting, ISO 14001, and green technology innovation) and dependent variables (financial performance), as well as the role of moderating variables (company size). The study's results indicate that green accounting and ISO 14001 have a positive impact on financial performance. Green technology innovation does not affect financial performance. Company size moderates the relationship between green accounting and ISO 14001 on financial performance, but does not moderate the effect of green technology innovation.